2002
DOI: 10.2190/jgjr-0kvl-hrf7-gcnv
|View full text |Cite
|
Sign up to set email alerts
|

Developing the Computer User Self-Efficacy (Cuse) Scale: Investigating the Relationship between Computer Self-Efficacy, Gender and Experience with Computers

Abstract: The article describes the development and validation of the 30-item Computer User Self-efficacy (CUSE) Scale. Self-efficacy beliefs have been identified as a factor which may contribute to the success with which a task is completed. Because of the increasing reliance on computer technologies in all aspects of life, it is important that the construct is measured accurately and appropriately. In particular, the article focuses on the measurement of computer self-efficacy in student computer users and its relevan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
324
4
23

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 343 publications
(370 citation statements)
references
References 14 publications
19
324
4
23
Order By: Relevance
“…The study is also limited in terms of limited sample information available. Individual differences such as previous experience using VLEs and computer and Internet user self-efficacy (Cassidy & Eachus, 2002;Eachus & Cassidy, 2006), approaches to learning and self-regulation (Cassidy, 2011) are likely to play a part in the efficacy of VLEs (Selim, 2007) and serve as examples of a range of potentially relevant factors that should be taken in to account in evaluation studies.…”
Section: Discussionmentioning
confidence: 99%
“…The study is also limited in terms of limited sample information available. Individual differences such as previous experience using VLEs and computer and Internet user self-efficacy (Cassidy & Eachus, 2002;Eachus & Cassidy, 2006), approaches to learning and self-regulation (Cassidy, 2011) are likely to play a part in the efficacy of VLEs (Selim, 2007) and serve as examples of a range of potentially relevant factors that should be taken in to account in evaluation studies.…”
Section: Discussionmentioning
confidence: 99%
“…Messineo and DeOllos (2005) discovered differences by gender and race/ethnicity. Some studies found that males reported higher results than females (Cassidy & Eachus, 2002).…”
Section: Computer Knowledgementioning
confidence: 99%
“…Heinrichs and Lim (2010) examined users' perceived functional skills and competency in word processing and presentation tools. Cassidy and Eachus (2002) created a computer user self-efficacy scale, in part because CSE has been identified as a success factor for the completion of computing tasks. They noted that a significant positive correlation between CSE and computer experience could be established, and familiarity with computer software was a significant predictor of CSE while computer ownership and training increased efficacy.…”
Section: International Journal Of Learning and Developmentmentioning
confidence: 99%
“…PTD involves not only mastering technological skills and concepts, but also the ability to learn new ways of using computers in a creative and personally meaningful way (Committee on Information Technology Literacy 1999). Items were adapted from the computer-user self-efficacy scale developed by Cassidy and Eachus (2002) and the Computer Attitude Questionnaire developed by the Texas Center for Educational Technology. The PTD competence subscale used in this study includes six items for adults and three for children.…”
Section: Data Collectionmentioning
confidence: 99%